Rekonstruksi Distribusi Soal Asesmen Kompetensi Minimum Kelas XI Bidang Literasi Membaca Berdasarkan Bentuk Soal - Salindri, Leni; Warisman, Guntur; Wagiran, Wagiran; Naryatmojo, Deby Luriawati (Universitas Tidar, 2024)
Current learning should be able to equip students to have the skills to use life skills in order to develop the potential of students. The goal of national education is to develop the potential of students to become a democratic and responsible Pancasila student profile. One attempt to raise the profile of critical and democratic students is through literacy activities. Kemendikbud organizes assessment activities entitled National Assessment as an evaluation of the education system. The National Assessment is directed at mapping the quality of input, process, and learning outcomes. (AKM). AKM consists of literacy reading and numeration. Previous research has shown that AKM is a tool to measure student skills, not only in mastering content, but also in improving students' ability to think critically and solve problems. In the context of reading literacy, this research will focus on reconstruction of AKM components in reading literature in high school. This research uses a qualitative research method approach to research on the conditions of natural objects. The source of the data in the research is about the AKM field of literacy reading class IX. Data is obtained through observations and interviews with informants. Data analysis techniques by means of data collection, data reduction, data presentation, and drawing conclusions. The results of the research showed that based on the form of the question, the AKM question consists of five forms of the matter: double choice, double choice complex, ridiculous, short filling and description